High impact litigation (2011)
Impact Litigation as an alternative strategy to practice Law,consists in the process of selecting, analyzing and developingsome cases that allows an important effect in the policies, thelaw and the society. With Impact Litigation some social problemsare selected, discussed and organized in legal, political andcommunicative problems in order to reach complete solutionsto those problems and the social change.